PENGEMBANGAN KOMIK BERBASIS MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS V MIN MEDAN SUNGGAL - Maulana Arafat Lubis; Reh Bungana Beru Perangin-angin; Deny Setiawan (JURNAL TEMATIK, 2018)
This research is aimed to know: (1) planning teaching of comic material form developed model of Based Learning on civics education learning as a main discussion of decision together (2) improving the result of students learning using teaching comic material basis of problem based learning model (3) the effectiveness of teaching comic material developed. The subjects of this research are the fifth grade students MIN Medan Sunggal at second semester at year 2015/2016 that has total 23 students. The total of men is 10 students and women is 13 students. The research is development research Research and Develoment/ R&D), model of ADDIE development has steps, namely: (1) analysis (2) designing (3) developing (4) implementation (5) evaluation.